ASPECTS REGARDING THE APPLICATION OF THE NORMS OF INTERNATIONAL HUMANITARIAN LAW IN THE SETTLEMENT OF THE TRANSNISTRIA, ABKHAZIA AND SOUTH OSSETIA CONFLICTS - Alexander KURTSKHALIA (Moldoscopie, 2020)
The fact that an international legal regime, especially an expansive legal regime, can be considered to be applicable in the regions of Transnistria, Abkhazia and South Ossetia is all the more significant, given the status of the regions as de facto states without obligations and possibility to apply international standards and norms, leaving the population of the regions without any international legal protection. From our point of view, the regime of international humanitarian law would provide a certain level of protection for the population condemning war crimes, such as rape, murder and torture, protecting civilian assets, and initiating criminal prosecution of alleged offenders. In all the cases in which the European Court found the extraterritorial jurisdiction and the foreign support of the separatist movements there were also revealed the violations of the rights protected by the Convention